2003
DOI: 10.1046/j.1532-5415.2003.51554.x
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms as a Risk Factor for Disabling Back Pain in Community‐Dwelling Older Persons

Abstract: The presence of depressive symptoms is a strong, independent, and highly prevalent risk factor for the occurrence of disabling back pain in community-dwelling older persons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 35 publications
5
62
0
2
Order By: Relevance
“…Our finding that high depression symptomatology increased the risk of LBP in the whole cohort is in line with previous work indicating that high levels of depressive symptoms predict future LBP in older individuals [8,10]. The underlying mechanisms remain largely unexplained but it has been posited that, in people with painful musculoskeletal conditions, depression symptomatology influences somatic, affective, behavioural and cognitive aspects of the pain experience [20].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our finding that high depression symptomatology increased the risk of LBP in the whole cohort is in line with previous work indicating that high levels of depressive symptoms predict future LBP in older individuals [8,10]. The underlying mechanisms remain largely unexplained but it has been posited that, in people with painful musculoskeletal conditions, depression symptomatology influences somatic, affective, behavioural and cognitive aspects of the pain experience [20].…”
Section: Discussionsupporting
confidence: 91%
“…Depression symptomatology is an independent risk factor for LBP and a frequent problem in the older, community living population [8]. A recent systematic review, including studies of seniors aged 75 years and older, found prevalence estimates of 7.2 % (95 % CI 4.4-10.6 %) for major depression and 17.1 % (95 % CI 9.7-26.1 %) for depressive disorders [9].…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have recently described severe back and/or neck pain as being strong predictors of major depression at a wide range of ages [26][27][28]. Currie and Wang [26] used the short form of the Composite International Diagnostic Interview to examine the prevalence and correlates of major depression in persons with chronic back pain using data from the Canadian Community Health Survey in a sample of 118 533 household residents.…”
Section: Low Back And/or Neck Painmentioning
confidence: 99%
“…In comparison with the lowest quartile of scores (the least depressed), those in the highest quartile of depression scores had a 4-fold increased risk of troublesome neck and low back pain. Carrington Reid et al [28] studied 754 members of a large health plan who were 70 years and older. They used a score of 16 or greater on the Center for Epidemiologic Studies-Depression Scale to identify the presence of depressive symptoms.…”
Section: Low Back And/or Neck Painmentioning
confidence: 99%
“…Depression is of concern in the elderly and can be precipitated or exacerbated by many factors, including back pain [12]. Importantly, depression in elderly patients with lower back pain could contribute to worse quality of life.…”
Section: Epidemiologymentioning
confidence: 99%